School connectedness and psychological resilience as mediators in the relationship between childhood abuse and suicidal ideation among Chinese adolescents. Issue 1 (31st December 2023) - Yang, Yinmei; Liu, Mingxiu; Cao, Na; Li, Xuyang; Chen, Zongshun; Kelifa, Mohammedhamid Osman
ABSTRACT: Background: Suicide among adolescents is a huge public health concern around the world. Although childhood abuse has been established as a substantial risk factor for suicide behaviours, potential mediators in this relationship remain unclear. Objective: This study aimed to examine the mediating roles of school connectedness and psychological resilience in the association between childhood abuse and suicidal ideation among Chinese high school students. Methods: The sample involved 1607 adolescents from four high schools in Central China. Structural equation modelling (SEM) was conducted to investigate the mediation effects of school connectedness and psychological resilience on the relationship between childhood abuse and suicidal ideation. Results: The prevalence of suicidal ideation during the past week was 21.9%. Childhood abuse was positively related to the development of suicidal ideation directly and indirectly through school connectedness and psychological resilience. School connectedness and psychological resilience were also partial mediators of all three types of childhood abuse (emotional abuse, physical abuse and sexual abuse) when the types were examined separately. Conclusions: Suicidal ideation was widespread among Chinese high school students. Psychological resilience and school connectedness could attenuate the detrimental impact of childhood abuse on suicidal ideation. Findings underscore the improvement of psychological resilience and the connection to the school would be beneficial to suicide prevention among Chinese adolescents with childhood abuse. HIGHLIGHTS: Adolescent suicide is a major public health concern worldwide. Childhood abuse exerts a negative effect on suicide behaviours. School connectedness and psychological resilience mediated the relationship between childhood abuse and suicidal ideation.